2023
DOI: 10.1021/acs.biochem.3c00095
|View full text |Cite
|
Sign up to set email alerts
|

PAP(248–286) Conformational Changes during the Lag Phase of Amyloid Fibril Formation

Abstract: The initial stage of fibril formation of C-terminal region PAP(248–286) of human seminal plasma protein prostatic acid phosphatase was considered. Amyloid fibrils from the peptide PAP(248–286) are termed as a semen-derived enhancer of viral infection (SEVI) found in abundant quantities in semen. The kinetics of the amyloid fibril formation process consists of two characteristic phases (lag phase/nucleation phase and growth phase/elongation phase). The lag phase can be caused by the presence of mature amyloid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Sexual transmission continues to be one of the primary modes of HIV transmission, with human semen serving as a vector for viral transmission, and women, in particular, at higher risk of contracting HIV through sexual contact. , One factor that has drawn the interest of the HIV research community is the role of a specific 39 amino acid-long peptide, PAP248–286, in the infection process. , PAP248–286 is derived from prostatic acid phosphatase (PAP), a protein present in high concentrations in human seminal fluid . Previous studies have suggested that PAP248–286 peptides play an important role in enhancing HIV infection by several folds. , PAP248–286 peptides aggregate to form amyloid fibrils termed semen-derived enhancers of viral infection (SEVI). ,, Unlike typical amyloid peptides, which mainly display biological activity when aggregated into fibrils, PAP248–286 has been reported to show biological activity even in its monomeric form. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual transmission continues to be one of the primary modes of HIV transmission, with human semen serving as a vector for viral transmission, and women, in particular, at higher risk of contracting HIV through sexual contact. , One factor that has drawn the interest of the HIV research community is the role of a specific 39 amino acid-long peptide, PAP248–286, in the infection process. , PAP248–286 is derived from prostatic acid phosphatase (PAP), a protein present in high concentrations in human seminal fluid . Previous studies have suggested that PAP248–286 peptides play an important role in enhancing HIV infection by several folds. , PAP248–286 peptides aggregate to form amyloid fibrils termed semen-derived enhancers of viral infection (SEVI). ,, Unlike typical amyloid peptides, which mainly display biological activity when aggregated into fibrils, PAP248–286 has been reported to show biological activity even in its monomeric form. , …”
Section: Introductionmentioning
confidence: 99%
“… 5 , 8 PAP248–286 peptides aggregate to form amyloid fibrils termed semen-derived enhancers of viral infection (SEVI). 5 , 9 , 10 Unlike typical amyloid peptides, which mainly display biological activity when aggregated into fibrils, PAP248–286 has been reported to show biological activity even in its monomeric form. 5 , 11 15 …”
Section: Introductionmentioning
confidence: 99%